2018
DOI: 10.1503/cmaj.170920
|View full text |Cite
|
Sign up to set email alerts
|

Care of community-dwelling older adults with dementia and their caregivers

Abstract: I n Canada, about 500 000 individuals are currently affected by dementia. 1,2 Caring for people with dementia is complex and costs the health system $15 billion annually. 1,2 The findings of qualitative studies involving people living with dementia and their caregivers have suggested that improvements in care and health care for these individuals would be welcomed. 3,4 Most individuals are first diagnosed and receive care for dementia in community or primary care settings; community-based services are the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Regarding the contribution of Andersen’s model predisposing factors to the explanation of forgone care, our study showed, similar to others [ 33 , 35 ], that having lower education was associated with increased forgone care for both caregivers and care-receivers. Although none of the examined enabling factors were associated with forgone care for the person with dementia, participants reporting lower levels of income had an increased likelihood to forgo care for themselves.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the contribution of Andersen’s model predisposing factors to the explanation of forgone care, our study showed, similar to others [ 33 , 35 ], that having lower education was associated with increased forgone care for both caregivers and care-receivers. Although none of the examined enabling factors were associated with forgone care for the person with dementia, participants reporting lower levels of income had an increased likelihood to forgo care for themselves.…”
Section: Discussionsupporting
confidence: 89%
“…For older adults receiving home care on a long-stay basis, a population at high risk of potentially inappropriate care transitions and associated adverse outcomes,2 3 we showed that the likelihood for LTC admission and death (but not urgent hospitalisation) for clients with compared with those without dementia was significantly modified by their frailty status. Given projected increases in the prevalence of both dementia and frailty,1 21 future work should examine the extent to which the quality, appropriateness and outcomes of health and social care services vary for persons with dementia43 and with varying degrees of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, 46 million people in the world had dementia; this number is expected to double every 20 years as the global population ages, reaching 131.5 million by 2050 [ 1 ]. Up to 70% of older adults with dementia live in private community dwellings [ 2 ] and the majority of their care is provided by primary care physicians (PCPs) [ 3 , 4 ]. Caring for older adults with dementia is complex; most have numerous medical comorbidities and are more likely to experience adverse side effects to commonly prescribed medicines [ 5 ].…”
Section: Introductionmentioning
confidence: 99%